Peningkatan Kapasitas Usaha melalui Penerapan Teknologi dan Perbaikan Manajemen pada Usaha Produksi Tempe skala Rumah Tangga di Kelurahan Cikaret Bogor Selatan - Ningtyas, Desinta Rahayu; Dewi Kurniawati; Gita Aprilia Timang; Vector Anggit Pratomo; Afrizal Fadrurahman Priyanto; Laelatul Ngazizah (LOSARI DIGITAL, 2025)
The tempeh business has the potential to grow, given that public consumption of tempeh remains high, but challenges remain in the traditional production process. This community service activity aims to enhance the capacity of household tempeh producers in Cikaret Village, South Bogor, by applying appropriate technology and improving business management. The implementation method was carried out in a participatory manner through several stages, which was activity coordination, procurement of soybean peeling equipment and fermentation rooms, business management counselling, assistance in technology implementation, and evaluation. The results of the activity showed an increase in production process efficiency of up to 50% with the use of soybean peeling and hulling machines. The application room improved the success of fermentation and the quality of tempeh. From a management perspective, the ability of partners to maintain financial records. This activity also raised collective awareness and the emergence of local leaders within the business group. This program demonstrates that the combination of technology and management improvements can strengthen the capacity, efficiency, and independence of small, household-based businesses.